Purification and characterization of a peptide from soybean with cancer cell proliferation inhibition. Issue 4 (21st March 2017) - Rayaprolu, Srinivas J.; Hettiarachchy, Navam S.; Horax, Ronny; Kumar‐Phillips, Geetha; Liyanage, Rohana; Lay, Jackson; Chen, Pengyin
Abstract: A peptide from protein hydrolysate fraction obtained from a high oleic acid soybean line (N98‐4445A) that had shown significant activity against human cancer cell lines was identified and purified. Three peptides showing highest activity were identified by reverse phase HPLC in the 10–50 kDa fraction of the protein and purified using peptide specific affinity chromatography column. The three individual peptides were tested for anti‐proliferative activity against blood, colon and liver cancer cell lines using 3‐(4, 5‐dimethyl thiazole‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) cell titer assay. Enhanced colon cancer cell inhibition (80%) was observed after testing a pure peptide (molecular size of 18 kDa with 158 amino acid residues) which also demonstrated a time‐response of 96 hr after incubation based on trypan blue dye exclusion study. The impact of this study lies in deriving a pure single peptide with anti‐proliferative activity on human colon and blood cancer cells. Practical applications: Soybean is cultivated in the United States mostly for extracting the oil leaving the residue (soybean meal) which is commonly used as an animal feed due to its high protein content. This study has shown that soy peptides produced enzymatically from the meal of a high oleic acid soybean line (N98‐4445A) were found to have anticancer activity. This study demonstrated an impending value for a pure peptide derived from this soy peptides as an alternative and inexpensive anti‐cancer therapeutic agent as well as a value addition to soy meal by‐product.